Comparative evaluation of label-free SINQ normalized spectral index quantitation in the central proteomics facilities pipeline. - Trudgian, D; Ridlova, G; Fischer, R; Mackeen, M; Ternette, N; Acuto, O; Kessler, B; Thomas, B (2011)
Normalized spectral index quantification was recently presented as an accurate method of label-free quantitation, which improved spectral counting by incorporating the intensities of peptide MS/MS fragment ions into the calculation of protein abundance. We present SINQ, a tool implementing this method within the framework of existing analysis software, our freely available central proteomics facilities pipeline (CPFP). We demonstrate, using data sets of protein standards acquired on a variety of mass spectrometers, that SINQ can rapidly provide useful estimates of the absolute quantity of proteins present in a medium-complexity sample. In addition, relative quantitation of standard proteins spiked into a complex lysate background and run without pre-fractionation produces accurate results at amounts above 1 fmol on column. We compare quantitation performance to various precursor intensity- and identification-based methods, including the normalized spectral abundance factor (NSAF), exponentially modified protein abundance index (emPAI), MaxQuant, and Progenesis LC-MS. We anticipate that the SINQ tool will be a useful asset for core facilities and individual laboratories that wish to produce quantitative MS data, but lack the necessary manpower to routinely support more complicated software workflows. SINQ is freely available to obtain and use as part of the central proteomics facilities pipeline, which is released under an open-source license.